PENGARUH PENGALAMAN AUDIT, KEAHLIAN AUDIT DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT BPK RI PERWAKILAN PROVINSI SULAWESI UTARA - Sanger, Christin Lisa; Ilat, Ventje; Pontoh, Winston (ACCOUNTABILITY, 2016)
This study aimed to examine the effect of audit experience, audit expertise, and obedience pressure to audit judgment taken by auditor. The sample of this research are auditors who worked on Badan Pemeriksa Keuangan (BPK) RI Representative of Nort Sulawesi Province. The sample was conducted by purposive sampling method. Collecting data was conducted by questionnare distributed directly to auditors as much 50 and only 38 questionnare replayed. Data analysis used multiple linear regression method with SPSS (Statistical Product and Service Solution). The result of this research showed that audit experience significantly affect audit judgment taken by auditor, obedience pressure significantly affect audit judgment taken by auditor, but audit expertise didn’t significantly affect audit judgment taken by auditor, because the audit expertise in variabel measurement only use indicator : adetailed knowledge of the financial statements, have the ability to perform an audit in accordance with the regulations and have many types of certification / recognition of the expertise of technical training (does not represent an operational definition of variables). So that the results are less present facts on the ground. Keywords: audit experience, audit expertise, obedience pressure, audit judgment.